The war at sea in the Mediterranean 1940-1944 - Grehan, John; Mace, Martin (Despatches from the front, 2014)
Despatches in this volume include those covering the Battle of Matapan in 1941, Fleet Air Arm operations in 1940, the Battle of Sirte in 1942, the action with the Italian Fleet off Calabria (Central Mediterranean) in 1940, the engagement between British and Italian forces off Cape Spartivento (Central Mediterranean) in 1940, the Mediterranean convoys between January 1941 and August 1942 - which includes the famous Operation Pedestal, operations in the Aegean in 1943, the engagement with an Italian convoy in 1941, and the despatch covering Coastal Force actions, including those in the Mediterranean. This unique collection of original documents will prove to be an invaluable resource for historians, students and all those interested in what was one of the most significant periods in British military history. The Coastal Forces despatch also includes those vessels assigned to the Levant, Dover and Nore stations - i.e. outside of the Mediterranean theatre.